Analisis Pengelolaan Modal Kerja Dalam Meningkatkan Profitabilitas Perusahaan Manufaktur Sub Sektor Food And Beverage Yang Terdaftar Di BEI - Tri Aryano Geovani; Aris Munandar (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
The purpose of this study is to identify and analyze working capital management in increasing the profitability of manufacturing companies in the food and beverage subsector. This research uses associative research with a quantitative approach. The sample in this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for the period 2016 – 2020 using the purposive sampling method. There are 4 companies that meet the criteria for the research sample, simultaneously showing that cash turnover, accounts receivable turnover, and inventory turnover simultaneously affect the profitability of the food and beverage subsector companies. Based on the test, it is known that partially shows that cash turnover and inventory turnover have an effect on profitability. Meanwhile, accounts receivable turnover has no partial effect.